The complete chloroplast genome sequence of the endemic and rare orchid Nothodoritis zhejiangensis (Orchidaceae) in China. Issue 10 (3rd October 2021) - Yang, Lei; Wu, Qi; Yang, Mingqi; Zhang, Dong; Dong, Shubin; Cheng, Jin
Abstract: Nothodoritis zhejiangensis (Orchidaceae) is a rare orchid unique to China of great horticultural value. The complete chloroplast (cp) genome of this species is 143, 522 bp in length and the total GC content is 36.8%. It includes a large single copy (LSC) region of 83, 830 bp in length, a small single copy (SSC) region of 10, 764 bp, and a pair of inverted repeat regions (IRs) with 24, 464 bp. The cp genome contains 120 functional genes, including 74 protein-coding genes, 38 tRNA genes, and eight rRNA genes. The phylogenetic tree constructed by the maximum-likelihood method showed that the taxonomic status of N. zhejiangensis was clustered with the species in Phalaenopsis .